2022
DOI: 10.3390/app12125877
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae as Potential Sources of Bioactive Compounds for Functional Foods and Pharmaceuticals

Abstract: Microalgae are an untapped source of bioactive compounds with various biotechnological applications. Several species are industrially produced and commercialized for the feed or cosmetic industries, however, other applications in the functional food and pharmaceutical markets can be foreseen. In this study, nine industrial/commercial species were evaluated for in vitro antioxidant, calcium-chelating, anti-tumoral, and anti-inflammatory activities. The most promising extracts were fractionated yielding several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…Increased pigment (carotenoid) extractability could not fully explain the increased antioxidant activity, which might be partly due to the presence of other compounds of microalgal or bacterial origin. Silva et al [ 82 ], for an ethyl acetate extract from the biomass of a commercial T. lutea , obtained an IC 50 of 0.8 g L −1 , more than half that for lipophilic extracts in this work (about 1.7–1.8 g L −1 ). A water extract from Pavlova lutheri KMCC H-006 fermented with the yeast Hansenula polymorpha showed an IC 50 value of 0.3 g L −1 [ 83 ], an activity much higher than that of the extract in 30% EtOH in water obtained from fermented biomass in the present work, which did not reach values exceeding 50%, making it impossible to calculate IC 50 .…”
Section: Discussionsupporting
confidence: 55%
“…Increased pigment (carotenoid) extractability could not fully explain the increased antioxidant activity, which might be partly due to the presence of other compounds of microalgal or bacterial origin. Silva et al [ 82 ], for an ethyl acetate extract from the biomass of a commercial T. lutea , obtained an IC 50 of 0.8 g L −1 , more than half that for lipophilic extracts in this work (about 1.7–1.8 g L −1 ). A water extract from Pavlova lutheri KMCC H-006 fermented with the yeast Hansenula polymorpha showed an IC 50 value of 0.3 g L −1 [ 83 ], an activity much higher than that of the extract in 30% EtOH in water obtained from fermented biomass in the present work, which did not reach values exceeding 50%, making it impossible to calculate IC 50 .…”
Section: Discussionsupporting
confidence: 55%
“…It was concluded that there was compelling evidence for the benefits of microalgal compounds, but further research on their digestive mechanism is required. This has been reiterated by other workers [82] [83] who posited that fermentation of microalgae has potential, but it is still a fairly new area. It was suggested that more work should be carried out to ascertain the true composition of microalgae to enable manipulation into other products.…”
Section: Mechanism Of Actions Of Microalgae Produced Bioactive Compoundsmentioning
confidence: 84%
“…The genetic diversity of microalgae is an unfathomed source of bioactive compounds for multivarious products, such as pharmaceuticals, nutraceuticals, biopesticides, and biostimulants (González‐Pérez et al, 2021; Silva et al, 2022). Plant biostimulants facilitate nutrient uptake, improve crop performance and tolerance to abiotic stress, and therefore can have a crucial role in reducing dependency on synthetic fertilizers and plant protection products, and thus address agronomic sustainability challenges (Chiaiese et al, 2018).…”
Section: Introductionmentioning
confidence: 99%